2016
DOI: 10.19125/jmrd.2016.2.2.35
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Prader-Willi Syndrome with Diabetes Mellitus

Abstract: Prader-Willi syndrome (PWS) often develops type 2 diabetes mellitus (T2DM) related to severe obesity. The prevalence of T2DM in adults with PWS (7-20%) exceeds greatly the prevalence in the general population (5-7%). It is uncommon for pre-pubertal children with PWS to develop overt diabetes or glucose intolerance. GH therapy and genotype did not influence the development of altered glucose metabolism. It has been assumed that T2DM in PWS develops as a consequence of morbid obesity and concomitant insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…187 By contrast, concomitant studies reported that approximately 25% of PWS individuals are diabetic in other European cohorts, 188,189 and even a higher percentage is suggested in an Asian population, with approximately 30% of T2DM incidence in PWS. 190 Despite the clear incidence of T2DM within PWS population, there are discrepant reports in the literature on the role of defective glucose-regulation in the pathophysiology of PWS. Furthermore, increased plasma concentrations of additional metabolism-controlling hormones (i.e.…”
Section: Insulinmentioning
confidence: 99%
“…187 By contrast, concomitant studies reported that approximately 25% of PWS individuals are diabetic in other European cohorts, 188,189 and even a higher percentage is suggested in an Asian population, with approximately 30% of T2DM incidence in PWS. 190 Despite the clear incidence of T2DM within PWS population, there are discrepant reports in the literature on the role of defective glucose-regulation in the pathophysiology of PWS. Furthermore, increased plasma concentrations of additional metabolism-controlling hormones (i.e.…”
Section: Insulinmentioning
confidence: 99%